{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

HO1-sol-2009

# HO1-sol-2009 - Homework 1 Solutions Problem 1 First we...

This preview shows pages 1–2. Sign up to view the full content.

Homework 1 Solutions January 24, 2009 Problem 1 First we check that X ( t ) is stationary. Let ( a 1 , . . . , a n ) be any n -tuple with a i = ± 1. We need to verify that P ( X ( t 1 ) = a 1 , X ( t 2 ) = a 2 , . . . , X ( t n ) = a n ) = P ( X ( t 1 + h ) = a 1 , X ( t 2 + h ) = a 2 , . . . , X ( t n + h ) = a n ) The left hand side has the form P [ X ( t 1 ) = a 1 , X ( t 2 ) = a 2 , . . . , X ( t n ) = a n ] = = P [ ξ ( - 1) N t 1 = a 1 , ξ ( - 1) N t 2 = a 2 , . . . , ξ ( - 1) N tn = a n ] = = P [ ξ ( - 1) N t 1 = a 1 , ξ ( - 1) N t 1 + N t 2 - N t 1 = a 2 , . . . , ξ ( - 1) N t n - 1 + N tn - N t n - 1 = a n ] = = P [ ξ ( - 1) N t 1 = a 1 , ( - 1) N t 2 - N t 1 = a 2 a 1 , . . . , ( - 1) N tn - N t n - 1 = a n a n - 1 ] = = P [ ξ ( - 1) N t 1 = a 1 ] P [( - 1) N t 2 - N t 1 = a 2 a 1 ] . . . P [( - 1) N tn - N t n - 1 = a n a n - 1 ] , where in the last step we used that the Poisson process N t has independent increments and ξ is independent of it. In the same way the right hand side has the form P [ ξ ( - 1) N t 1 = a 1 ] P [( - 1) N t 2 + h - N t 1 + h = a 2 a 1 ] . . . P [( - 1) N tn + h - N t n - 1 + h = a n a n - 1 ] Now noting that the random variables N t i + h - N t i - 1 + h and N t i - N t i - 1 have the same (Poisson, parameter t i - t i +1 ) distribution we see that the above expressions are identical except for the first terms. But since ξ and N t are independent P [ ξ ( - 1) N s = 1] = P [ ξ = 1] P [( - 1) N s = 1] + P [ ξ = - 1] P [( - 1) N s = - 1] = = 1 / 2 ( P [( - 1) N s = 1] + P [( - 1) N s = - 1] ) = 1 / 2 and similarly P [ ξ ( - 1) N s = - 1] = 1 / 2, so they do not depend on s . This means that the first terms in the products are also the same. We have thus verified directly that X ( t ) is stationary. Now we compute the mean and covariance (autocorrelation). The mean is easy, since E [ ξ ] = 0 implies E [ X ( t )] = E [ ξ ( - 1) N t ] = E [ ξ ] E [( - 1) N t ] = 0. To find the covariance, suppose that s t , so that R ( X t , X s ) = E [ X t X s ] = E [ | ξ 2 ( - 1) N t + N s | ] = E [( - 1) N t - N s +2 N s ] = E [( - 1) N t - N s ] = = ( - 1) P ( N t - N s = odd) + (1) P ( N t - N s = even) = 1 - 2 P ( N t - N s = odd) To compute the latter observe that N t - N s is Poisson with parameter t - s and so P ( N t - N s = odd) = summationdisplay k =0 e - λ λ 2 k +1 (2 k + 1)! = e - λ e λ - e - λ 2 = 1 - e - 2 λ 2 .

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}